Motives for consumer choice of traditional food and European food in mainland China. (1st April 2015) - Wang, Ou; De Steur, Hans; Gellynck, Xavier; Verbeke, Wim
Highlights: Presents a Food Choice Questionnaire-based study in mainland China Proposes a novel construct with six food choice motive dimensions "Time or money saving" and "Sensory appeal" are key food choice motives Traditional food choices are driven by "Availability and familiarity" Preference for European food is linked to "Mood" motives Abstract: The demand for European (-style) foods in mainland China has been increasing dramatically during the last decade. Nevertheless, European food producers often appear to be not capable to fully exploit this huge market potential, partially due to the competition with traditional (Chinese) foods. This study examines the determinants of mainland Chinese consumers' choice of traditional food and European food. A web-based survey was administered with 541 consumers from two cities: Shanghai and Xi'an. Thereby, the Food Choice Motives model, predominantly used thus far in a European or developed context, is applied to mainland China in order to address the lack of knowledge on food motives of its consumer market and to detect associations between these motives, attitudes, and purchase intentions. Factor analysis resulted in a new Food Choice Motive construct that is considered more appropriate within the context of mainland Chinese consumers, encompassing six dimensions: Health concern, Time or money saving, Sensory appeal, Availability and familiarity, Mood and Food safety concern . Path analysis demonstrated that Time or money saving was negatively associated with attitude toward traditional food on the one hand and purchase intentions toward European food on the other hand. Availability and familiarity had a positive association with attitude toward traditional food. Mood was a positive factor driving attitude toward European food. For both food types, Sensory appeal and Attitude were positively linked to purchase intentions. Furthermore, Mood was negatively linked to the purchase intention toward traditional food in Shanghai. Food safety concern was positively associated with attitudes toward traditional food in Xi'an.